Implementation of the Indonesian Association of Anesthesia Technicians (IPAI) Role in Developing Professional Standards for Anesthesia Technicians - Ni Luh Putu Indah Sari; I Gusti Ngurah Parikesit Widiatedja (Indonesian Journal of Global Health Research, 2025)
The Indonesian Association of Nurse Anesthetists (IPAI) plays a crucial role in strengthening the professional standards of Nurse Anesthetists, particularly through the formulation of competency standards, codes of ethics, and the implementation of credentialing mechanisms. This study aims to analyze the implementation of IPAI’s strategic role within the applicable legal framework, particularly referring to the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/1416/2023. The research employs a normative juridical method with a descriptive qualitative approach, utilizing The primary data sources consisted of statutory regulations, including the Decree of the Minister of Health No. HK.01.07/MENKES/1416/2023, Law No. 36 of 2014, Law No. 17 of 2023, and Minister of Health Regulation No. 34 of 2020.and secondary data from the documentation of the Bali Provincial Board of IPAI. The findings indicate that although IPAI has obtained normative legitimacy within the national health law system, the implementation of its organizational functions still encounters several obstacles. These include uneven distribution of members across regions, weak regulatory enforcement for healthcare facilities, and limited involvement of IPAI in the credentialing process, all of which contribute to disparities in service quality. Furthermore, the absence of sanction provisions in KMK 1416/2023 leads to low compliance with the established professional standards. Therefore, regulatory harmonization between the KMK and Law Number 17 of 2023, institutional strengthening of IPAI at the regional level, increased legal literacy among health professionals, and the integration of a cross-sectoral digital credentialing system are necessary.